Sealing the Leak: A Prospective Study on Risk Factors and Outcomes of Expectant Management in Preterm Premature Rupture of Membranes - Jagathiswari, P.S.; M, Rajalekshmi; senathirajah, Tharaka (Journal of Neonatal Surgery, 2025)
Background: Preterm premature rupture of membranes (PPROM) is a significant contributor to perinatal morbidity and mortality. This study evaluates risk factors, clinical presentation, and outcomes of expectant management in antenatal women with PPROM between 28 and 37 weeks of gestation. Methods: A prospective observational study was conducted at Saveetha Medical College from January 2023 to March 2024. Twenty-one antenatal women with singleton pregnancies complicated by PPROM were enrolled. Clinical, microbiological, and neonatal outcomes were assessed. Data were analyzed using SPSS v21, with p-values ≤0.05 considered statistically significant. Results: Most patients presented within 11 hours of membrane rupture. The most common organisms identified were E. coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. Conservative management led to favorable outcomes in early PPROM. Neonatal morbidities included jaundice and birth asphyxia (12% each), and one stillbirth was recorded. Chorioamnionitis and urinary tract infections were key maternal complications. Conclusion: Expectant management in stable early PPROM cases, supported by antibiotics and corticosteroids, can lead to improved neonatal outcomes. However, strict monitoring is vital to detect complications such as chorioamnionitis